Koordinasi Badan Narkotika Nasional dan Polres Dalam Mencegah Peredaran Gelap Narkotika di Kota Kendari - Anggreny, Dini; Tarifu, La; Taufik, Taufik (REZ PUBLICA, 2021)
This research aims to determine the coordination between the BNN and the Police in Preventing the Illicit Trafficking of Narcotics and the Factors Affecting the Coordination of the National Narcotics Agency with the Resort Police in Preventing the Illicit Trafficking of Narcotics in Kendari City. This type of research is qualitative descriptive with 7 people selected according to purposive sampling. Sources of data in this research are primary and secondary data, which were collected through observation, interviews and documentation.The results of this research indicate that the Internal Coordination Form, BNN and Polres in preventing illicit narcotics trafficking in Kendari City are said to have carried out their obligations as responsible officers by providing data and information to each institution. The form of External Coordination between BNN and Polres is communication and providing information between each other so that in the division of tasks it is considered that there are no obstacles but there are several factors that affect BNN coordination with the Resort Police, including unity of action, communication, division of labor, and discipline due to lack of awareness apparatus in their duties and responsibilities so that there is still overlap between the BNN and the Polres.